The role of TRPA1 channels in thermosensation - Zhang, Hao; Wang, Chengsan; Zhang, Keyi; Kamau, Peter Muiruri; Luo, Anna; Tian, Lifeng; Lai, Ren (Cell insight, 2022)
Transient receptor potential ankyrin 1 (TRPA1) is a polymodal nonselective cation channel sensitive to different physical and chemical stimuli. TRPA1 is associated with many important physiological functions in different species and thus is involved in different degrees of evolution. TRPA1 acts as a polymodal receptor for the perceiving of irritating chemicals, cold, heat, and mechanical sensations in various animal species. Numerous studies have supported many functions of TRPA1, but its temperature-sensing function remains controversial. Although TRPA1 is widely distributed in both invertebrates and vertebrates, and plays a crucial role in tempreture sensing, the role of TRPA1 thermosensation and molecular temperature sensitivity are species-specific. In this review, we summarize the temperature-sensing role of TRPA1 orthologues in terms of molecular, cellular, and behavioural levels.